Penerapan Strategi Pembelajaran Terbalik (ReciprocalTeaching) Untuk Meningkatkan Komunikasi Matematika(Pada Siswa Kelas Vii Smp Muhammadiyah 4 Sambi 2015/2016) - Fajar Purwaningtias, Wahyu, Rita P. Khotimah, S. Si., M. Sc (2016)
The background of the problem in this study is the weak of communication skill math class VII student of SMP Muhammadiyah 4 Sambi C. The purpose of this study to describe the improvement of SMP Muhammadiyah 4 Sambi student is communication skill math by using Reciprocal Teaching strategi. This study belongs to action class research. The technique of collecting data are observation, testing, field notes, and documentation. The results showed that the improvement of SMP Muhammadiyah 4 Sambi student in the mathematical communication skills can be seen from: 1. Convey mathematical ideas verbally from before 8 students (36.36%) and after the action increase become 12 students (54.54%) 2. Convey mathematical ideas in writing from before 10 students (45.45%) and after the action increase become 18 students (81.81%) 3. Convey mathematical ideas through pictures from before 6 students (27.27%) and after the action become 13 students (59.09%) 4. Explain mathematical concepts from before 7 students and after the action increase become 14 students (63.63%). Based on the data above can be concluded that the applying of Reciprocal Teaching strategi can improve communications skills math.